EFFECTS OF NECK BANDS ON REPRODUCTION AND SURVIVAL OF FEMALE GREATER SNOW GEESE - Reed, Eric; Gauthier, Gilles; Pradel, Roger (HAL CCSD, 2005)
International audience An assumption of mark-recapture studies is that the marker has no effect on the animal. Neck bands have been used extensively for goose research, but there has long been concern that they may have negative effects on some demographic parameters, and recent studies have yielded contradictory results. We evaluated the effects of neck bands on adult female greater snow geese (Chen caerulescens atlantica) by contrasting breeding propensity and apparent survival of geese marked with both a plastic neck band and a metal leg band and those marked solely with metal leg bands over an 11-year period on Bylot Island, Nunavut Territory. The use of multistate mark-recapture models also allowed us to estimate neck band loss and to obtain survival and capture probabilities that were not biased by such loss. Finally, we tested the effects of neck bands on other reproductive parameters (laying date, clutch size and nest success) over a 3-year period. Neck-banded females had decreased clutch size and capture probabilities, but their apparent survival rate, nest initiation and hatching dates, and nest survival were not affected compared to leg-banded only or unbanded females. Breeding propensity, indexed by capture probabilities of neck-banded females was, on average, 48% lower that that of leg-banded-only females but clutch size was only 10% lower. Neck band loss of females was low in this population (3% per year). We urge researchers to be cautious in the use of neck bands for estimation of population parameters, and that the potential negative effects of neck bands be assessed as it is likely to be species-specific. JOURNAL OF WILDLIFE MANAGEMENT 69(1):91-100, 2005